Réinscrire la convivialité: connectivités queer du culinaire chez Abdellah Taïa - Dubois, Philippe C. (Modern & contemporary France, 2021)
Although Abdellah Taïa has often been celebrated for his queer positioning and the boldness with which he discusses dissident forms of sexuality in Morocco, little critical attention has been given to his ingenious use of food practices as tools for reconfiguring desires and instruments of domination. Through the study of three novels figuring his subjugation to expressions of power both in Morocco and in France, this essay examines the culinary discourse as a forceful narrative in the service of the expansion of notions of conviviality and of belonging. A close look at his rerouting of gender and sexual borders from the centre to the periphery will also unearth in the suburbs of Paris the existence of interstitial spaces fraught with tensions between solidarity and destruction, where queer and transnational connections to the world can be reformulated.